Effectiveness of auriculotherapy in the management of oncology patients: Integrative review (Research, Society and Development, 2024)
Introduction: The duality between cancer treatment and its side effects is a major challenge for health professionals. In this context, auriculotherapy emerges as a technique that promotes symptom relief and improves the quality of life in cancer patients in a complementary way. Objective: to identify the effectiveness of auriculotherapy in managing symptoms in cancer patients. Methodology: Integrative literature review guided by the Health Sciences Descriptors (DeCS), namely: auriculotherapy; ear acupuncture; cancer, quality of life, including publications from the period between January 2018 and November 2023, in Portuguese and/or translated into Portuguese in the Virtual Health Library (BVS) and SciELO databases. The articles were classified using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results: The literature search for 21 unique articles, leaving only 8 articles at the end. Of these, the majority (87.5%) had a high level of evidence, which highlights the reliability of the information. Furthermore, all studies found positive effects associated with auriculotherapy, with the exception of one study, which had significant limitations. Conclusion: Integrative auriculotherapy therapy is a unique and indispensable non-pharmacological strategy in providing complementary care to cancer patients, having effects on pain relief, reducing anxiety and depression, as well as fatigue, stress, nausea and vomiting, being a safe and well-tolerated intervention, with only mild side effects.